1992
DOI: 10.1016/0142-727x(92)90004-s
|View full text |Cite
|
Sign up to set email alerts
|

Laminar/turbulent oscillating flow in circular pipes

Abstract: A two-dimensional oscillating flow analysis was conducted simulating the gas flow inside Stirling engine heat exchangers. Both laminar and turbulent oscillating pipe flow were investigated numerically for Remax=l,920 (Va=80), 10,800 (Va=272), 19,300 (Va = 272), and 60,800 (Va = 126). The results are here compared with experimental results of previous investigators. Predictions of the flow regime on present oscillating flow conditions are also checked by comparing velocity amplitudes and phase difference with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…6(a) where no trace of a transition is identified, the evolution of the turbulence kinetic energy is smooth with its amplitude proportional to the sinusoidal cross-sectional velocity. Similar results are previously reported by Ahn and Ibrahim [22]. In the derivation of the standard keε turbulence model, the assumption is that the flow is fully turbulent, and that the effects of molecular viscosity are negligible, therefore, the model is only valid for fully turbulent flow.…”
Section: Transitional Reciprocating Pipe Flowsupporting
confidence: 80%
See 2 more Smart Citations
“…6(a) where no trace of a transition is identified, the evolution of the turbulence kinetic energy is smooth with its amplitude proportional to the sinusoidal cross-sectional velocity. Similar results are previously reported by Ahn and Ibrahim [22]. In the derivation of the standard keε turbulence model, the assumption is that the flow is fully turbulent, and that the effects of molecular viscosity are negligible, therefore, the model is only valid for fully turbulent flow.…”
Section: Transitional Reciprocating Pipe Flowsupporting
confidence: 80%
“…The transition from laminar to turbulent flow has been given a great deal of attention in the existing literature [11,17,18,20,22,32]. Experimental measurements show that the onset of turbulence in a reciprocating flow is different from that of a steady flow.…”
Section: Reciprocating Flow Assessmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Fortunately, Seume and Simon [36] have experimentally observed that no flow separation occurred in oscillating turbulent flows. In fact, Ahn and Ibrahim [37] successfully used the standard k-e model with the help of the wall function method for such an oscillating turbulent flow. Although flow reversal may occur in a pulsating turbulent flow with a large velocity oscillating amplitude, it can be confidently inferred that no flow separation would develop in the pulsating turbulent flow.…”
Section: Turbulent Modelmentioning
confidence: 99%
“…According to the previous studies on the transition to turbulence of oscillatory pipe flows, the critical boundary Reynolds number for transition,  Re , was unanimously found to be around 500-550 [34][35][36][37], where…”
Section: Experimental Apparatus and Conditionsmentioning
confidence: 99%